Assessment of Epicardial Fat Thickness in Infants of Diabetic Mothers and its Relation to Glycated Albumin Level - Abdou, Rania Mohamed; El Raggal, Nehal Mohamed; Mansour Elsayed, Rania Ashraf Yehia; Salah Eldin, Nanies Mohammed (International Journal of Child Health and Nutrition, 2025)
Background: Infants of diabetic mothers (IDMs) are at increased risk for developing cardiometabolic disorders. Traditional markers like HbA1c have limitations in certain clinical scenarios, highlighting the need for alternative indicators. Epicardial fat thickness (EFT), due to its anatomical and functional proximity to the heart, and glycated albumin, a short-term glycemic marker, may provide early risk detection. Objective: To assess epicardial fat thickness and umbilical cord glycated albumin levels in neonates of diabetic mothers and determine their association, exploring their potential as early predictors of short-term glycemic control and cardiometabolic risk. Methods: This cross-sectional, case-control study involved 35 IDMs and 30 neonates born to non-diabetic mothers (NIDMs). Echocardiography measured EFT in the first week of life, while glycated albumin was measured via ELISA from umbilical cord blood. Statistical analysis included ROC curves and logistic regression to evaluate diagnostic performance. Results: EFT and glycated albumin were significantly elevated in IDMs compared to NIDMs (p < 0.001). A cutoff value of EFT >16.3 mm had a specificity of 93.1% and a sensitivity of 54.29%. Glycated albumin>434 g/dl showed a sensitivity of 91.43% and specificity of 83.33%. Multivariate analysis identified glycated albumin as a strong independent predictor of pregestational diabetes mellitus, while both biomarkers were associated with gestational diabetes. Conclusions: EFT and glycated albumin serve as effective, non-invasive markers for early detection of cardiometabolic risk in neonates born to diabetic mothers. Their incorporation into routine assessments may enhance early diagnosis and targeted intervention strategies.